Do you sincerely want to be rich? Bernard Cornfeld and I.O.S.: an international swindle - Raw, Charles; Hodgson, Godfrey; Page, Bruce (London : Deutsch, 1971)
This book is about the ambition of Bernard Cornfeld to make Investors Overseas Services the most important economic force in the Free World. The company which encouraged people to invest in shares turn out to be an avenue for swindling people of their money.
Includes index
Includes bibliographical references.
usc 10/04/18
Loans
Keywords: Cornfeld, Bernie